Did the February 6-7 Türkiye Earthquake Trigger a Housing Market Bubble? Empirical Insights from Right-tailed Unit-root Tests - Gökhan Kartal (İstanbul İktisat Dergisi)
This study primarily aims to assess whether the destructive earthquakes of February 6-7, 2023 triggered a potential nationwide housing market bubble. Spanning the period from January 2010 to September 2024, the analysis employs Generalised Supremum Augmented Dickey-Fuller and Backward Supremum Augmented Dickey-Fuller methods to identify bubble formations. The findings reveal significant bubble periods, including January to August 2015, November 2015 to November 2016, May 2018 to January 2019, May to June 2019, and February to December 2023. The latest bubble formation occurred immediately after the earthquake, highlighting a strong link between the disaster and housing market dynamics. While the earthquake’s impact—through abrupt housing stock loss, large-scale displacement, and intensified demand for secure housing—was undeniably a crucial trigger for this bubble, other macroeconomic factors, such as inflationary pressures, low interest rates, and the perception of housing as a lucrative investment, also played a reinforcing role. The Türkiye experience enhances the understanding of speculative cycles in seismic regions, demonstrating how non-economic shocks such as earthquakes can rapidly boost demand and strain housing supply, amplifying speculative behaviour. This bubble, which peaked in May 2023 and gradually deflated, completely dissipated by December 2023. This development can be associated with the policies implemented by economic authorities, including interest rate hikes, restrictive credit measures, as well as the normalisation of conditions across the country following the earthquake. This highlights the need for proactive monitoring and intervention by economic authorities through appropriate economic policies and regulations to address supply-demand imbalances and mitigate the risks of future housing bubbles, particularly in response to external shocks. Furthermore, in response to the study’s findings on earthquake-triggered bubbles, policymakers should prioritise initiatives aimed at strengthening building infrastructure and implementing urban transformation strategies.